K-pop, Cultura Fandom e Transmídia: um estudo de caso do grupo sul-coreano ATEEZ - GIOVANA GOMES FLORES (2024)
Part of the Hallyu Wave – a phenomenon based on the exportation of South Korean culture – K-pop conquered its space in global pop culture. Among the groups that make up the South Korean music industry, the tendency to develop transmedia narratives emerged with the third generation of the genre and continues to this day. The present work has the general objective of analyzing how the development of these narratives interferes with the consumption experience of K-pop fandoms, taking as its object of study the K-pop group ATEEZ, whose fictional storyline portrays the adventure of a group of 8 young men who travel between dimensions and through time. Among the elements analyzed in the research are: the construction of the group's fictional universe, how the insertion of narrative elements influences the public's interest in the content and how fans interact with the plot during ATEEZ releases. To this purpose, three research methods were applied to collect data: an online questionnaire, using the plataform Google Forms, a mapping carried out on the social network X and a non-participant observation on a Discord server composed by fans of the group. From the information collected, it was possible to identify the importance of narrative in the consumption process of the fandom, who actively engage with content through social networks and discussion forums, acting collaboratively in search of information that can contribute to understanding the narrative developed by the artists.